Pola Asuh Pasangan Suami Istri Bekerja dan Perilaku Menyimpang Anak - Intan Maharani Adiningtyas; Sri Budi Lestari (Interaksi Online, 2021)
Nurturing pattern in family brought consequences to children’s behavior, for example, nurturing pattern of a married couple which only one of them that work. Nurturing pattern involves communication between parents and children, so that communication becomes important in the relationship between parents and child. This study aimed to describe nurturing pattern of married couple who both work, in relations of the children’s deviant behavior. Using an interpretive paradigm with a qualitative descriptive approach. The research subjects were three married couples who both work puts ide the house and have children in their teens. The theory that been used is the Theory of Family Communication Pattern and Theory of Relational Dialectics. The results of this study indicate that protective pattern, laissez faire pattern and pluralistic patterns that previously being predicted were found in this study. The protective pattern was found in couple number 1 which characterized by a low conversational orientation and a high conformity orientation. A low conversation orientation is characterized by a lack of communication and openness between couples 1 and the child. Meanwhile, a high conformity orientation is characterized by determining guidelines or what kind of rules for their children to do and the children being led to obey the rules of their parents. The laissez faire pattern were found in couple 2 which characterized by a low conversational orientation and conformity orientation. Minimal conversation activity also lacks of assertiveness and involvement between parents and children on a daily basis. Meanwhile, the pluralistic pattern were found in couple 3 is characterized by a high conversational orientation and a low conformity orientation. The talk activity between parents and children who fairly frequent so there is a child's openness to the parents. Meanwhile, a low conformity orientation is characterized by a lack of firmness about the rules and limits of children's behavior and tends to free their children for doing something. Despite having different nurturing pattern, the three married couples who both worked, found deviant behavior in their children. The deviant behavior that was found are different from one couple’s child to another, but the form of deviant behavior was the same, namely deviant non-conforming behavior.